"Association of periodontopathic anaerobic bacterial co-occurrence to atherosclerosis" – A cross-sectional study. (April 2017) - Mahalakshmi, Krishnan; Krishnan, Padma; Arumugam, Sarasa Bharathi
Abstract: Background: Epidemiological studies have shown a link between periodontitis and atherosclerosis. Hence the present study was chosen to assess the presence of eight anaerobic periodontal pathogens and their virulence genes in subgingival plaque (SGP) and atheromatous plaque (AP) of patients with Ischaemic heart disease. Methods: SGP and AP collected from 65 Ischaemic heart disease patients were screened for the presence of periodontal bacterial pathogens by Polymerase chain reaction. The samples positive for Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia were screened for virulence genes. Chronic periodontitis patients (ChP) without any systemic disease (n = 59) and healthy subjects free of both periodontitis and systemic disease were included as control groups (n = 100). Results and discussion: Statistical significance was observed for the prevalence of 16S rRNA of P. gingivalis, T. forsythia, T. denticola and P. nigrescens both in SGP and AP. Nine different periodontal bacterial co-occurrences were observed in SGP and AP of Ischaemic heart disease patients. Besides, the prevalence of these nine different bacterial co-occurrence was high in SGP OF Ischaemic heart disease patients compared to ChP without systemic disease. Among the nine different bacterial co-occurrence, only four were observed in SGP of ChP without systemic disease in spite of high prevalence of these anaerobic bacterial species. While, bacterial co-occurrences was completely absent among healthy subjects. Significant odds and risk ratio to atherosclerosis were observed for P. gingivalis, T. forsythia, T. denticola and P. nigrescens . Among the virulence genes, significance to atherosclerosis was observed for P. gingivalis type II fimA and T. forsythia bspA . Conclusion: The results of this study strongly correlate periodontal bacterial co-occurrence and periodontal bacterial adhesion factor to atherosclerosis. Highlights: Nine different bacterial co-occurrences were detected in the SGP and AP of atherosclerosis patients. In the SGP of ChP patients without systemic disease only four different bacterial co-occurrences was observed. Bacterial co-occurrence was totally absent among the healthy subjects. The presence of these bacterial co-occurrences within the same patient's SGP and AP strongly link them to atherosclerosis.